Measurements of equatorial plasma depletion velocity using 630 nm airglow imaging over a low‐latitude Indian station. Issue 1 (7th January 2014) - Taori, A.; Sindhya, A.
Abstract [1] We report the east‐west velocity measurements of the equatorial plasma depletion (EPD) from Gadanki (13.5°N, 79.2°E, dip latitude 6.5°N) estimated using the airglow imaging of O(1D) 630 nm airglow emission during the years 2012–2013. Our measured EPD velocity values are significantly smaller than earlier reported values from low‐latitude stations in India. The measured nocturnal EPD velocity variations are compared with recent empirical model given by England and Immel (2012). We note that during March–April months, our measurements agree very well with the empirical model while minor differences are noted in other months. We also note the differences between our measurements and horizontal wind model. We believe that these differences suggest the deviation of electrodynamics associated with EPD from the one occurring in the background thermospheric altitudes.